Emergence - New England Complex Systems Institute; Institute for the Study of Coherence and Emergence; Complexity Society (Mahwah, NJ : Lawrence Erlbaum Associates, 1999)
"A journal of complexity issues in organizational management" (varies).
Imprint varies; published: Mansfield, MA : ISCE Pub., <2005->
Vol. 1, no. 1- called also: Vol. 1, issue 1-
Some no. combined.
Mode of access: World Wide Web.
Vol. 1, no. 1-v. 1, no. 2 issued by: New England Complex Systems Institute; v. 1, no. 3- by: Institute for the Study of Coherence and Emergence; and, the Complexity Society, 2004-
Description based on: Vol. 2, no. 1 (2000); title from journal information page (OCLC FirstSearch Web site, viewed Oct. 26, 2000).
Keywords: Management -- Periodicals; Complex organizations -- Periodicals; Complexity (Philosophy) -- Periodicals; Complex organizations; Complexity (Philosophy); Management; Electronic journals